2011
DOI: 10.1093/geronb/gbr050
|View full text |Cite
|
Sign up to set email alerts
|

Does Self-reported Health Bias the Measurement of Health Inequalities in U.S. Adults? Evidence Using Anchoring Vignettes From the Health and Retirement Study

Abstract: These results suggest caution in relying on self-reported health measures to quantify and explain health disparities by socioeconomic status and race/ethnicity/ethnicity in the United States. The findings support expansion of the use of anchoring vignettes to properly account for reporting differences in self-reports of health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 55 publications
2
104
0
1
Order By: Relevance
“…322,[330][331][332][333] Clinical assessments can also be influenced by patients' characteristics; for instance, fat mass and bony structure affect the reliability and validity of extremity measurements, 334 while age and vulnerability may influence communication with health professionals or interviewers. 335 Performance testing may not always assess ADL of relevance to an individual and may not take into account environmental or behavioural adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…322,[330][331][332][333] Clinical assessments can also be influenced by patients' characteristics; for instance, fat mass and bony structure affect the reliability and validity of extremity measurements, 334 while age and vulnerability may influence communication with health professionals or interviewers. 335 Performance testing may not always assess ADL of relevance to an individual and may not take into account environmental or behavioural adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…African Americans and Hispanic Americans might have underestimated their sleep problems. One recent study, for example, revealed that African and Hispanic respondents were relatively optimistic in their ratings than Whites [41]. Studies that deploy objective measures of sleep behavior and sleep quality may overcome limitations associated with reliance on self-reported sleep measures.…”
Section: Discussionmentioning
confidence: 99%
“…describe differences across groups in, for example, the types and scope of health factors considered, the reference groups used in comparisons, definitions of health, interpretation and use of the response scale, and interpretation of other aspects of the survey question (Jylhä 2009). Aspects of this phenomenon have also been referred to as "reporting differences" (Burgard and Chen 2014), "reporting heterogeneity" (Lindeboom and van Doorslaer 2004;Dowd and Todd 2011;Dowd 2012), or "differential item functioning" (Grol-Prokopczyk, Freese, and Hauser 2011). Evidence for differences in evaluative frameworks across social groups is found in studies that highlight differences in SRH across groups among individuals that are otherwise similarly situated with respect to health factors, or differences in health outcomes (including mortality) across groups among individuals with similar SRH ratings.…”
Section: Socialmentioning
confidence: 99%